A numerical assessment of ocean alkalinity enhancement efficiency on a river-dominated continental shelf—a case study in the northern Gulf of Mexico - Yanda Ou; Z George Xue; Xinping Hu (Environmental Research Letters)
A robust high-resolution coupled hydrodynamic-biogeochemical model was applied to the northern Gulf of Mexico to assess the efficiency of river- and ocean-sourced ocean alkalinity enhancement (OAE). Sensitivity tests indicate that the effectiveness of OAE-induced CO _2 uptake is primarily influenced by the amount of alkalinity introduced and local wind-driven mixing, with the former determining the overall uptake and the latter affecting short-term variability. Compared to ocean-sourced OAE (direct ocean release), river-sourced OAE (elevated river alkalinity) is more effective and sustainable. River-sourced OAE has higher CO _2 uptake efficiency with reduced spatial and temporal uncertainty and greater overall CO _2 uptake. For river-sourced OAE, surface pH increases pronouncedly near the mouths of the Mississippi River. The ideal OAE implementation time includes spring, early summer, fall, and winter. Mid and late-summer implementation is not recommended due to weak mixing, which results in less alkalinity dispersal and greater pH variability. In addition, while the aragonite saturation state generally remains below 6 around the Mississippi River plume, it increases pronouncedly during mid to late summer, risking alkalinity loss due to CaCO _3 precipitation and reduced CO _2 uptake efficiency near river mouths. Scaling OAE-induced CO _2 uptake to the 25 largest rivers in the world indicates that increasing riverine alkalinity concentrations by 10% could remove 23.23 megatons of CO _2 annually, meeting 0.37%–0.61% of the 2025–2030 CO _2 removal target.